(untitled) - O'Leary Timothy J. (Boston, 2002)
The mission of the series is to build upon and extend this interest by not only teaching the specific application skills but by introducing the concepts that are common to all applications, providing students with the confidence, knowledge, and ability to easily learn the next generation of applications
Keywords: Electronic spreadsheets,Excel ( Computer programs ),Programming languages ( Electronic computers )